Answer:
Part A:
The solution to the pair of equations represented by p(x) and f(x)
is (2 , -1)
Part B:
(1 , 1) and (3 , -3) are the two solutions for f(x)
Part C:
The solution to the pair of equations represented by g(x) = f(x) is (0 , 3)
Step-by-step explanation:
* Lets study the three graphs
- g(x) is an exponential function where f(x) = 2 + (1.5)^x
- g(x) intersect the y-axis at point (0 , 3)
- g(x) intersected f(x) at point (0 , 3)
- f(x) is a linear function passing through point (3 , -3) , (1 , 1)
- The slop of f(x) = 1 - -3/1 - 3 = 4/-2 = -2
- f(x) intersect y-axis at point (0 , 3)
- f(x) = -2x + 3
- f(x) intersect x-axis at point (1.5 , 0)
- f(x) intersected p(x) at point (2 , -1)
- p(x) is a linear function passing through point (4 , 2) , (2 , -1)
- The slop of p(x) = -1 - 2/2 - 4 = -3/-2 = 3/2
- p(x) intersect y-axis at point (0 , -4)
- p(x) = 3/2 x - 4
- p(x) intersect x-axis at point (8/3 , 0)
* Now lets solve the problem
* Part A:
∵ p(x) meet f(x) at point (2 , -1)
∴ The solution to the pair of equations represented by p(x) and f(x)
is (2 , -1)
* Part B:
∵ f(x) passing through (1 , 1) and (3 , -3)
∴ (1 , 1) and (3 , -3) are the two solutions for f(x)
∵ g(x) meet f(x) at point (0 , 3)
∴ The solution to the pair of equations represented by g(x) = f(x)
is (0 , 3)